2013
DOI: 10.1038/ng.2813
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies frequent inactivating mutations in BAP1, ARID1A and PBRM1 in intrahepatic cholangiocarcinomas

Abstract: Through exomic sequencing of 32 intrahepatic cholangiocarcinomas, we discovered frequent inactivating mutations in multiple chromatin-remodeling genes (including BAP1, ARID1A and PBRM1), and mutation in one of these genes occurred in almost half of the carcinomas sequenced. We also identified frequent mutations at previously reported hotspots in the IDH1 and IDH2 genes encoding metabolic enzymes in intrahepatic cholangiocarcinomas. In contrast, TP53 was the most frequently altered gene in a series of nine gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

48
562
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 590 publications
(622 citation statements)
references
References 21 publications
48
562
11
1
Order By: Relevance
“…TP53 is mutated in 39 (38.2%) of this cohort of ICC patients, a frequency within the range of frequencies reported in some previous studies targeting TP53 in ICCs, but is substantially higher than many frequencies reported previously. For example, this frequency is much higher than that (6%) reported in the cohort of 32 ICC patients treated at various hospitals in the United States of America 24 , that (9.8%) reported in the cohort of 41 ICC patients from Singapore 23 and that (8.9%) reported in the cohort of 45 ICC patients from Romania 23 . These patients (who are from Singapore and Romania) and patients studied here do not have liver fluke infection, suggesting that factors other than liver fluke infection contributed to the differences in mutation prevalence.…”
Section: Mutationmentioning
confidence: 59%
See 4 more Smart Citations
“…TP53 is mutated in 39 (38.2%) of this cohort of ICC patients, a frequency within the range of frequencies reported in some previous studies targeting TP53 in ICCs, but is substantially higher than many frequencies reported previously. For example, this frequency is much higher than that (6%) reported in the cohort of 32 ICC patients treated at various hospitals in the United States of America 24 , that (9.8%) reported in the cohort of 41 ICC patients from Singapore 23 and that (8.9%) reported in the cohort of 45 ICC patients from Romania 23 . These patients (who are from Singapore and Romania) and patients studied here do not have liver fluke infection, suggesting that factors other than liver fluke infection contributed to the differences in mutation prevalence.…”
Section: Mutationmentioning
confidence: 59%
“…This study suggests a unique role of mutations in PTEN in the tumorigenesis of ICC. Similarly, although mutations in ARID1A have not been found in a previous study on a cohort of 54 ICC patients with liver fluke infection, mutations in this gene have been found in two recent studies with larger sample sizes 23,24 , suggesting the importance of obtaining larger cohorts of ICC patients in mutation discovery studies. They have also been reported in multiple HCC cancer genomics [12][13][14] .…”
Section: Mutationmentioning
confidence: 84%
See 3 more Smart Citations